Clinical Significance of DPYD Gene Polymorphism Testing in Colorectal Cancer Patients Receiving Fluoropyrimidine-Based Chemotherapy: A Single-Center Study in Latvia - Sofija Vilisova; Aija Gerina (European Scientific Journal, ESJ, 2026)
Background: Fluoropyrimidine-based chemotherapy, including 5-fluorouracil (5-FU) and capecitabine, is a cornerstone of colorectal cancer (CRC) treatment. However, treatment-related toxicity varies substantially among patients and is influenced by pharmacogenetic factors. Variants in the DPYD gene, which encodes the enzyme dihydropyrimidine dehydrogenase (DPD), are associated with reduced enzyme activity and an increased risk of severe toxicity. Aim: To evaluate the prevalence of clinically relevant DPYD polymorphisms in Latvian CRC patients receiving fluoropyrimidine-based chemotherapy and assess the clinical impact of genotype-guided dose adjustment. Methods: This single-center observational study included 46 patients with histologically confirmed CRC treated at Pauls Stradiņš Clinical University Hospital. Patients were divided into retrospective and prospective cohorts. Genotyping was performed for four clinically relevant DPYD variants (c.1905+1G>A, c.1679T>G, c.2846A>T, and c.1236G>A). Clinical data, treatment modifications, and toxicity outcomes were analyzed. Toxicity was graded according to CTCAE criteria. Descriptive statistics and Pearson's chi-square test were used for statistical analysis. Results: Chemotherapy-related toxicity occurred in 20/46 patients (43.5%), while severe toxicity (grade 3–4) occurred in 6/46 patients (13.0%). Clinically relevant DPYD variants were detected in 2/46 patients (4.3%). One prospectively identified carrier underwent genotype-guided dose reduction, and no chemotherapy-related toxicity was observed. Age >70 years was significantly associated with dose reduction (p=0.02). The distribution of chemotherapy-related toxicity grades differed significantly across the three age groups (p = 0.042). Conclusion: DPYD testing appears feasible and potentially useful in routine oncology practice. However, its clinical impact could not be definitively assessed in this small cohort because of the limited number of DPYD variant carriers. Larger multicenter studies are needed to determine its impact on treatment safety and toxicity reduction.